Microbial Taxa Distribution Is Associated with Ecological Trophic Cascades along an Elevation Gradient - Yao, Fei; Yang, Shan; Wang, Zhirui; Wang, Xue; Ye, Ji; Wang, Xugao; DeBruyn, Jennifer M.; Feng, Xue; Jiang, Yong; Li, Hui (Frontiers in Microbiology, 2017)
The elevational pattern of soil microbial diversity along mountain slopes has received considerable interest over the last decade. An increasing amount of taxonomic data on soil microbial community composition along elevation gradients have been collected, however the trophic patterns and environmental drivers of elevational changes remain largely unclear. Here, we examined the distribution patterns of major soil bacterial and fungal taxa along the northern slope of Changbai Mountain, Northeast China, at five typical vegetation types located between 740 and 2691 m above sea level. Elevational patterns of the relative abundance of specific microbial taxa could be partially explained by the oligotrophic-copiotrophic theory. Specifically, two dark-coniferous forests, located at mid-elevation sites, were considered to be oligotrophic habitats, with relatively higher soil C/N ratio and NH4+-N concentrations. As expected, oligotrophic microbial taxa, belonging to the bacterial phyla Acidobacteria and Gemmatimonadetes, and fungal phylum Basidiomycota, were predominant in the two dark-coniferous forests, exhibiting a mid-elevation maximum pattern. In contrast, the broad leaf-Korean pine mixed forest located at the foot of the mountain, Betula ermanii-dominated forest located below the tree line, and alpine tundra at the highest elevation were considered more copiotrophic habitats, characterized by higher substrate-induced-respiration rates and NO3--N concentrations. Microbial taxa considered to be so called copiotrophic members, such as bacterial phyla Proteobacteria and Actinobacteria, and fungal phylum Ascomycota, were relatively abundant in these locations, resulting in a mid-elevation minimum pattern. At finer taxonomic levels, the two most abundant proteobacterial classes, alpha- and beta-Proteobacteria, along with Acidobacteria Gp1, 2, 3, 15, and the Basidiomycotal class of Tremellomycetes were classified with the copiotrophic group. Gamma- and delta-Proteobacteria, Acidobacteria Gp4, 6, 7, 16, and Basidiomycotal class of Agaricomycetes were classified as oligotrophic taxa. This work uses the oligotrophic-copiotrophic theory to explain the elevational distribution pattern of the relative abundance of specific microbial taxa, confirming some of the existing trophic classifications of microbial taxa and expanding on the theory to include a broader range of taxonomic levels.